Innovative functionalized carbon fibers from waste: How to enhance polymer composites properties. (15th April 2018) - Khan, Aamer; Jagdale, Pravin; Castellino, Micaela; Rovere, Massimo; Jehangir, Qasim; Mandracci, Pietro; Rosso, Carlo; Tagliaferro, Alberto
Abstract: Carbon fibers (CF) were synthesized from waste clothes and treated with oxygen plasma at 100 W and 200 W for 5 min. Surface morphology and structure of the treated CF were studied via Field Emission Scanning Electron Microscopy (FESEM) and Raman spectroscopy. The functional groups on the surface of the plasma treated CF were studied through X-Ray Photoelectron Spectroscopy (XPS) and Fourier Transform Infrared spectroscopy (FTIR). BET analysis showed that surface area of the fibers increases after treatment. The plasma treated CF retained higher amount of the epoxy resin in the wettability test. Composites were fabricated from untreated and treated CF in 1% and 3% by weight with epoxy resin. Mechanical and tribology behavior of the composites showed that the plasma treated CF composites are superior to their untreated counterparts. Morphology of the mechanical and the tribology specimen was studied with FESEM.